An exploratory study on employment reception towards the communication tools in Davao Light and Power Company - Amor, Charina Jane L.
This study explored the communication tools used by Davao Light and Power Company. The purpose of this study is to have an internal communication assessment through employee reception on the organization's communication tools. Moreover, it also analyzed the dynamics of employee reception towards the communication tool to use for a specific message. The subject of this research involved employees of Davao Light and Power Company Main Office. Both quantitative and qualitative research methods were used to address the research problems of this study. Survey questionnaires, one-on-one and informal interviews were administered to gather the data needed for the study. The data gathered were analyzed through Uses and Gratifications Theory and Adaptive Structuration Theory. The results of this study revealed that Davao Light and Power Company's internal communications highly characterized by horizontal communication. DLPC employees use different communication tools across the departments to process routine messages. Electronic mail, phone call and face to face conversation were the most used communication tools, while the least used communication tools were text messaging and bulletin board. The results of employee reception showed that the formal and informal communication tools have limitations. In order to fill the communication need, employees tend to use an alternative communication tools such as phone calls, face to face conversation and text messaging as reinforcement when the preferred medium cannot facilitate the necessary feedback. Generally, the research concluded that the employee reception has been an effective basis for internal communication assessment. Email was found to be the widely used communication tool; however, it still needs reinforcement especially when clarifications and immediate feedback are both needed. Text messaging, on the other hand, may be the least used communication tool but the usefulness of this medium is highlighted in situations where the rest of the media could fill in the communication need of the organization. Thus, having various communication tools for internal communication is practically an advantage to big organizations